The larvae of Athripsodes longispinosus longispinosus (Martynov 1909), Athripsodes longispinosus paleochora (Malicky 1972), and Athripsodes bilineatus aegeus Malicky 1999 (Trichoptera: Leptoceridae), including a discriminatory matrix to the larvae of genus Athripsodes Billberg 1820 in Greece - Waringer, Johann; Malicky, Hans (Zootaxa, 2019)
Larvae of three leptocerid caddisfly subspecies described in the present paper were sampled in Greece and the North Aegean island of Gökceada (Turkey). Information on the morphology of the final larval instar of each is given and the most important diagnostic features are illustrated. The subspecies are integrated into a synoptic discriminatory matrix including the currently known larvae of Greek species of genus Athripsodes. The species can be easily separated by head coloration; the morphology of the ventral apotome; setal and spinal patterns on the metadorsum, foretibiae, and anal prolegs; and by distribution. With respect to distribution, Athripsodes longispinosus longispinosus is known from Bulgaria, the Caucasus area, Turkey, the northern Greek mainland, and the Greek islands of Thasos, Lesbos, Andros, Ikaria, Naxos, and Rhodes. Athripsodes longispinosus paleochora is an endemic of the Greek island of Crete, and A. bilineatus aegeus has been recorded from the Peloponnese; the Greek islands of Euboea, Skiathos, Kithira, Andros; and Turkey.